Report of the WHO technical consulatation on the effects of maternal influenza and influenza vaccination on the developing fetus: Montreal, Canada, September 30 - October 1, 2015 - Fell, D; Bhutta, Z; Hutcheon, J; Karron, R; Knight, M; Kramer, M; Monto, A; Swamy, G; Ortiz, J; Savitz, D (Elsevier, 2017)
In 2012, the World Health Organization (WHO) released a position paper on influenza vaccination recommending that pregnant women have the highest priority for seasonal vaccination in countries where the initiation or expansion of influenza immunization programs is under consideration. Although the primary goal of the WHO recommendation is to prevent influenza illness in pregnant women, the potential benefits of maternal immunization in protecting young infants are also recognized. The extent to which maternal influenza vaccination may prevent adverse birth outcomes such as preterm birth or small-for-gestational-age birth, however, is unclear as available studies are in disagreement. To inform WHO about the empirical evidence relating to possible benefits of influenza vaccination on birth outcomes, a consultation of experts was held in Montreal, Canada, September 30–October 1, 2015. Presentations and discussions covered a broad range of issues, including influenza virus infection during pregnancy and its effect on the health of the mother and the fetus, possible biological mechanisms for adverse birth outcomes following maternal influenza illness, evidence on birth outcomes following influenza illness during pregnancy, evidence from both observational studies and randomized controlled trials on birth outcomes following influenza vaccination of pregnant women, and methodological issues. This report provides an overview of the presentations, discussions and conclusions.